Fundamentals of Arc Spraying Physical and Chemical Regularities - Boronenkov, Vladislav; Korobov, Yury.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book guides readers through the systematic analysis of Arc Spraying: one of the most widespread and important thermal spraying methods. Along the way, readers from industry and research laboratories become familiar with the features of the process and physical-chemical regulations of particles in flight, coating formation, internal coating properties, and their output parameters. The book is ideal for engineers, technicians, and scientists engaged in welding and thermal spraying and stands as an excellent reference for students interested in advanced coatings technology.
Conception of Arc Spraying Method -- Input Parameters of the Coating Process -- Coatings' Properties and External Influences -- Output Coatings Parameters.
Keywords: Coatings; Tribology; Corrosion and anti-corrosives.; Surfaces (Technology).; Thin films; Metals; Industrial engineering; Production engineering; Coatings; Tribology; Corrosion; Surfaces, Interfaces and Thin Film; Metals and Alloys; Industrial and Production Engineering